Spread of Drug-Resistant Pulmonary Tuberculosis in Estonia - Krüüner, Annika (American Society for Microbiology, 2001)
Restriction fragment length polymorphism (RFLP) analysis of 209 Mycobacterium tuberculosis clinical isolates obtained from newly detected pulmonary tuberculosis patients (151 male and 58 female; mean age, 41 years) in Estonia during 1994 showed that 61 isolates (29%) belonged to a genetically closely related group of isolates, family A, with a predominant IS6110 banding pattern. These strains shared the majority of their IS6110 DNA-containing restriction fragments, representing a predominant banding pattern (similarity, >65%). This family A comprised 12 clusters of identical isolates, and the largest cluster comprised 10 strains. The majority (87.5%) of all multidrug-resistant (MDR) isolates, 67.2% of all isolates with any drug resistance, but only 12% of the fully susceptible isolates of M. tuberculosis belonged to family A. These strains were confirmed by spoligotyping as members of the Beijing genotype family. The spread of Beijing genotype MDR M. tuberculosis strains was also frequently seen in 1997 to 1999. The members of this homogenous group of drug-resistant M. tuberculosis strains have contributed substantially to the continual emergence of drug-resistant tuberculosis all over Estonia.